Eastern boundary currents off North-West Africa - Pelegrí, Josep L.; Peña-Izquierdo, Jesús (IOC-UNESCO, 2015)
The Cape Verde Front (CVF) separates the North Atlantic subtropical gyre (NASG) from the north-eastern North Atlantic tropical gyre (NATG). Within the NASG, the Canary Current (CC) and the Canary Upwelling Current (CUC) comprise a relatively shallow (down to about 200-300 m) flow of North Atlantic Central Waters (NACW): the CC is found far offshore as a wide and poorly defined current while the CUC is a near-slope intense baroclinic jet linked to the coastal upwelling front. Within the top 300 m of the NATG, the along-slope Mauritania Current and the Cape Verde Current (CVC, a north-eastern extension of the North Equatorial Counter Current that broadly rotates around the Guinea Dome) carry South Atlantic Central Waters northwards. As a result, the frontal system is the site of intense along-slope flow convergence and offshore transport in the top 300 m of the water column. Further deep, down to some 500 m, the interior flow is very weak in both gyres, likely dominated by mesoscale features, except along the continental slope, where the northward Poleward Undercurrent (PUC) feeds through localized inputs from the interior ocean; in particular, within the NATG the CVC appears as responsible for southward transfer of NACW, across the CVF, which eventually reaches the PUC. Published